Prevention of Communicable Diseases in Infants in Indonesia - W. A. F. J. Tumbelaka; Sri Rochani Sudjarwo (Paediatrica Indonesiana, 1980)
Indonesia consists of more than 3000 islands. In 1979 the population is estimated to be 145 million. Communicable diseases and malnutrition are major health problems in rural and urban areas. Poverty, ignorance, exploitation of the environment and resources and ill health are responsible for the high childhood morbidity and mortality. Fifty percent of all deaths occur in the Under- Fives' group and infant mortality constitutes half of it. The communicable diseases are: 1. diseases related to poor hygienic and sanitary conditions, 2. disease preventable through immunizations, 3. vector borne diseases, 4. diseases transmitted through direct contact. The Indonesian Ministry of Health has identified the following health problems: environmental problems due to physical and biological factors, environmental problems due to socio-cultural factors including lack of community participation, problems due to the unsatisfactory health status of the community, health manpower problems, problems due to inefficiency in management and health facilities. Improvement of health service delivery system is done by means of a better outreach to the rural districts, giving priority to the low-income groups and encouraging the community's participation in health activities. Simple, inexpensive methods should be used which are adapted to the conditions and way of life of the community in the prevention of communicable diseases in infants.